The EPPO/OLAF compendium of national procedures: Estonia - Hauck, Pierre; Schneider, Jan-Martin; Karakocaoğlu, Nur Sena; Laird, Alastair Alexander; Ginter, Jaan; Justus Liebig University Giessen (My University, 2026)
This Estonian EPPO/OLAF volume provides a comprehensive collection of material for EPPO/OLAF investigations, including case law, sources of law, and relevant institutions. In addition, it contains a compendium of national statutory law related to EPPO/OLAF investigations, highlighting the process of criminal investigations. Finally, it deals with OLAF investigations in Estonia, focusing on the investigation mandates of the European Anti-Fraud Office and its national partners. Prof Dr Jaan Ginter has acted as the publication’s national expert.
Keywords: ddc:340; ddc:320